The Role of the International Law in Protection of the Cultural Property in Armed Conflict - Haneen Jamal Abduallah Alamoudi; Rawa Ghazy Abdulwahed Almakky (International Journal of Law Research and Studies, 2025)
Cultural heritage forms the link between people’s present and past, and most countries are keen to preserve this connection. However, perceptions of cultural heritage vary depending on people’s awareness of the importance of their heritage, on the one hand, and the extent to which other countries provide care and protection for their cultural heritage, on the other. Cultural property has received significant attention in the legal world and legal studies, particularly in public international law, due to its significant cultural and humanitarian value to peoples and countries, and its status as an extension of civilization and a symbol of scientific and cultural progress. Throughout the ages, humanity has suffered from the scourge of wars and the accompanying destruction, vandalism, smuggling, and attacks on such property, particularly during international and non-international armed conflicts. Conventions relating to this property were concluded during armed conflicts, with the aim of providing international protection and protecting such property from the threat of destruction. In this research, I shed light on the concept of cultural property, highlighting the threats to cultural heritage and international efforts to mitigate them in light of what is stated in international charters and treaties, and international, regional, Arab and Islamic organizations and their role in protecting, managing and promoting cultural heritage, and detailing the importance of cultural heritage, its significance and methods of protecting it.